Advanced nanomaterials : synthesis, properties and applications - Thomas, Sabu; Aneesh, P. M. (Boca Raton, Florida: Apple Academic Press, 2015)
A collection of highly selected, peer-reviewed chapters, this book showcases the research of an international roster of scientists. It covers nanomaterials with emphasis on synthesis, characterization, and applications. It also presents emerging developments in nanotechnology in areas as diverse as medicine, energy, electronics, and agriculture. In addition to engineering aspects, the book discusses the physics, chemistry and biotechnology behind the fabrication and device designing.
'This book is the collection of peer reviewed-papers presented at the second international conference on nanomaterials: synthesis, characterization, and application in January 2012 (ICN 2012) in Kottayam, India, that showcased the research of an international roster of scientists and students.'
Includes bibliographical references at the end of each chapters.
Keywords: Nanostructured materials -- Congresses; Nanotechnology -- Congresses